A comparison between Islamic and conventional bond fund’s performance in Malaysia - Koo, Von Siong (2015)
The main objective for an investment is to curb inflation. Unit trust is one of common investment vehicle in Malaysia. The main purpose of this study is to compare the performance analysis on Islamic bond funds and Conventional bond funds in Malaysia. The performance of both funds was analyzed over a period of 48 months commencing from January 2011 to December 2014. The monthly returns of 20 bond funds, being 10 Islamic bond funds and 10 Conventional bond funds are extracted from Morningstar system. Performance of unit trust always influenced by risk and return. In this research, the fund performances are evaluated by using six performance measures namely mean return, standard deviation, beta, Treynor index, Sharpe index and Jensen index. The results of this study suggest that Islamic Bond Funds are outperformed the Conventional bond funds during the period of study. On the other hand, Conventional bond funds seem to have a lower risk than Islamic bond funds. Nevertheless, when both funds are compared by using t-Test and ANOVA, results displayed Islamic bond funds and Conventional bond funds have no difference in fund‟s performance. The findings are highly relevant to investors as well as fund managers